Maternal serum alpha-fetoprotein and diabetes mellitus. - Wald, N; Cuckle, H; Boreham, J; Stirrat, G; Turnbull, A (1979)
Maternal serum alpha-fetoprotein (AFP) levels were measured from 12 to 24 weeks gestation in 27 singleton pregnancies in women with insulin-dependent diabetes mellitus and 90 controls without diabetes who were matched for gestational age. The geometric mean AFP level among the diabetic pregnancies was 60 per cent of that in the controls, a difference which was statistically significant (P less than 0.01). The difference in AFP level between diabetic patients and controls was most marked in sera taken before 21 weeks gestation.